AN ACTİVİTY PROPOSAL ON RESPECT FOR DİFFERENCES İN THE SOCİAL STUDİES CURRİCULUM (Third Sector Social Economic Review, 2021)
This research aims to present an actionable activity to teachers about respect for differences in the social studies curriculum. In addition, it is aimed to reveal the importance of the activities in finding the corresponding subject in the students. For this purpose, in the current research, an activity named ""Our Differences Are Our Wealth"" has been prepared in the present study. The implementation of the activity was carried out in a primary school in the central district of Aksaray province in the 2020-2021 academic year. It was observed that the students were willing to participate in this activity, which was carried out with fourth grade students. In addition, students stated that after the negative atmosphere of the Covid 19 epidemic, such entertaining lesson activities made them happy. As a result of the activity, the students stated that they had heard many things from their teachers about respect for differences before, but that they addressed this issue for the first time with such an activity and they were happy. In addition, they invited researchers again to their lessons for activities related to different subjects and the course was completed in this way.
Keywords: Social studies; respect for differences; efficiency